Examining the relationship between agile adoption motivation factors and agile practice clusters used by software startups in Kingdom of Saudi Arabia - Al-Sakkaf, Abdullah Mohammed Hussein (2016)
Agile software development methodology (ASDM) has been increasingly adopted in organizations. Despite many benefits offered by ASDM, successful ASDM adoption is a big challenge for organizations. Many studies show that these methods were adopted partly by selecting a set of agile practices. Therefore, it is difficult for new adopters to choose agile practice sets that fit their organization needs as ASDM has a big pool of available practices or clusters. Agile practices should be selected based on motivation factors that include the organization needs in order to maximize the benefit of adopting them. The aim of this study is to identify the relationships between organization’s ASDM adoption motivation factors and the agile practices clusters. This study used a quantitative approach to evaluate the relationships between these variables. The study was conducted using a questionnaire with 76 software practitioners from software startups in the Kingdom of Saudi Arabia (KSA). The analysis generated 4 clusters; each is associated with a list of practices. These clusters are labeled as project management, quality assurance, software process, and incremental and iterative clusters. This study finds that three adoption motivation factors (a motivation for increased software quality, increased efficiency, or increased effectiveness) are associated with the quality assurance, software process, and incremental and iterative clusters. By understanding these factors in terms of ASDM adoption and which types of agile practice cluster is more suitable will help to increase the success of the agile adoption process. Furthermore, the study will help to understand how the startups selected the practices used. Also, the study could help new startups to easily choose the proper agile practices based on their motivation and needs. The findings will help the organization to select suitable agile practices cluster by matching the motivation factors that correspondingly affect the ASDM successful adoption.